Pemberdayaan Bidan dalam Penerapan Hypnopressure untuk Meningkatkan Persiapan Laktasi - Nurbaiti Nurbaiti; Gustina Gustina; Laida Sanilpa Tiwi; Tuhu Perwitasari; Suci Rahmani Nurita (Jurnal Abdimas Kesehatan (JAK), 2026)
Breast milk is the primary source of nutrition for babies, containing complete nutrients and antibodies essential for growth and immunity. Global and Indonesian exclusive breastfeeding coverage remains suboptimal, including in Jambi Province, which remains below the national target. Low exclusive breastfeeding coverage is influenced by various factors, including maternal stress, lack of family support, inadequate lactation preparation, and insufficient milk production. One effort to improve the success of exclusive breastfeeding is through non-pharmacological approaches such as hypnopressure.This activity aims to change knowledge about hypnopressure and the formation of a hypnopressure class in preparation for lactation. This activity was carried out at TPMB Latifah Nur which was held on February 15, 2025, the target in this activity was three midwives at TPMB Latifah Nur, the media used was a booklet with lecture, question and answer, discussion methods, to measure knowledge before being carried out.mini workshop then the team didpretestby providing a questionnaire with 10 questions about hypnopressure in preparation for lactation aftermini workshop done post test. The activity implementation time is 1 day 1-2 hours. The results of this activity are changes in the increased knowledge of midwives abouthypnopressur In preparation for lactation, the initial knowledge was quite good at 66.7%, but after the mini workshop, the knowledge became good at 100% and the midwives were willing to inform pregnant women who visited the TPMB and form classes for pregnant women in preparation for lactation.